Biological N2 Fixation in Soybean and Contribution to Soil in a 40-Year-Old Experiment on Alfisols of Ranchi - B.K. Agrawal and Pankaj Sharma, Muneshwar Singh, R.H. Wanjari (Journal of the Indian Society of Soil Science, 2014)
To assess the impact of nutrient management on soybean-wheat productivity and to evaluate atmospheric N2-fixation potential of soybean under different nutrient management option, long-term (40-year-old) field experiment with various combinations of nutrients being conducted under AICRP-LTFE on Alfisols of Ranchi was used for the computation of atmospheric N2-fixation. The results revealed that to sustain productivity of soybean-wheat system over a long period of time balanced nutrient application with soil amendment either as lime or FYM is essential. The use of N alone (urea) without P and K and ammonium sulphate even with P and K had adverse effect on productivity of system. Atmospheric N2-fixation study clearly indicated that to harness N2-fixation capacity of soybean, we should grow soybean with balanced nutrition and then only we can offset N derived by soybean from soil through biologically fixed N of residual biomass of soybean and would lead positive balance of N in soil. Application of lime or FYM along with NPK resulted in maximum per cent N derived from atmosphere (%Ndfa) by soybean in Alfisols of Ranchi. Application of lime and FYM over and above 100% NPK added 36.0 and 36.3 kg N ha-1, respectively, which is greater than any of the treatments studied.